Lifestyle-Associated Acute Gastritis in a Young Adult : A Family Medicine Perspective on Holistic Management - Nur Rakhmani, Alidha; Dasa Novita, Khuznita; Fairuz Adani, Safira (Family Medicine Department, Faculty of Medicine, Brawijaya University, 2025)
Acute gastritis, a prevalent gastrointestinal condition, is often affected by lifestyle and psychosocial factors, requiring a comprehensive approach in primary care. This case report highlights the presentation, contributing factors, and comprehensive management of acute gastritis in a young adult, underscoring the essential role of family medicine principles in this context. We present the case of a 30-year-old female translator suffering from acute epigastric pain, clinically diagnosed as acute gastritis. Her condition worsened due to irregular eating habits, excessive intake of spicy foods and coffee, late sleeping hours, and work-related stress. The patient's symptoms are consistent with known risk factors for gastritis, such as eating habits, caffeine consumption, and mental stress. Although pharmacological intervention alleviated symptoms, the reemergence of symptoms following dietary indiscretion highlighted the significance of non-pharmacological approaches. The Family APGAR score indicated that the family was functioning at a moderate level, suggesting areas where communication and support could be improved. Our intervention focused on patient-centered education, emphasizing lifestyle modification, stress management, and promoting family support. This case demonstrates that acute gastritis in young adults frequently arises from alterable lifestyle factors. Effective management extends beyond simply prescribing medicine. It also includes teaching them about their condition, encouraging them to adopt healthy habits, helping them manage stress, and providing support from family and friends, all of which are important aspects of family medicine.